2021
DOI: 10.2147/prbm.s340209
|View full text |Cite
|
Sign up to set email alerts
|

All Normal Occupations are Sunny and Joyful: Qualitative Analysis of Thai Ladyboys’ Occupational Wellbeing

Abstract: Background As the modern social division of labour is becoming increasingly specified, various occupations have emerged. Ladyboy, as a special occupation, is receiving a surging amount of attention from society and academia. Ladyboy is an individual who is engaged in performing with female psychology but still retains male sexual characteristics, and this special characteristic has an impact on their occupational identity and occupational satisfaction. Methods This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The work environment in family firms can significantly influence employee job satisfaction, particularly during external shocks such as the COVID-19 pandemic ( Lyu et al, 2021 ). Previous research on socioemotional wealth has demonstrated that family businesses prioritize non-financial goals, including fostering altruism within the family and the organization ( Schulze et al, 2003 ) and building strong social ties with employees ( Block, 2010 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The work environment in family firms can significantly influence employee job satisfaction, particularly during external shocks such as the COVID-19 pandemic ( Lyu et al, 2021 ). Previous research on socioemotional wealth has demonstrated that family businesses prioritize non-financial goals, including fostering altruism within the family and the organization ( Schulze et al, 2003 ) and building strong social ties with employees ( Block, 2010 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Stakeholders are any group of people who can influence or be influenced by the organization's behavior, such as the public, investors, suppliers, and shareholders [ 39 ]. As a valuable intangible asset, reputational assets can attract customers, generate investment interest, improve financial performance, attract top employee talent, increase return on assets, and create a competitive advantage [ 40 , 41 ]. Stakeholders compare what they know about the organization to some standard to determine if it meets their expectations of how it should behave.…”
Section: Literature Review and Theory Backgroundmentioning
confidence: 99%
“…In the historical process of industrialization, population agglomeration to urban areas forms economies of scale and unified large markets, global economic growth lifts a wave of social urbanization, and metropolis form shaped population and economic resources in space polarization, thereby, exerting a significantly inhibiting effect on fertility. As a result of this, urbanization and low fertility rate gradually develop a dynamic docking relationship [ 4 , 20 , 27 , 28 , 45 ]. Since the Industrial Revolution, both emerging and developed nations have witnessed the phenomenon of “low fertility”, with fertility rates below the population replacement level.…”
Section: Brief Literature Review and Theoretical Hypothesismentioning
confidence: 99%